2007
DOI: 10.1007/s00586-007-0492-x
|View full text |Cite
|
Sign up to set email alerts
|

High failure rate of the interspinous distraction device (X-Stop) for the treatment of lumbar spinal stenosis caused by degenerative spondylolisthesis

Abstract: The X-Stop interspinous distraction device has shown to be an attractive alternative to conventional surgical procedures in the treatment of symptomatic degenerative lumbar spinal stenosis. However, the effectiveness of the X-Stop in symptomatic degenerative lumbar spinal stenosis caused by degenerative spondylolisthesis is not known. A cohort of 12 consecutive patients with symptomatic lumbar spinal stenosis caused by degenerative spondylolisthesis were treated with the X-Stop interspinous distraction device.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
1
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(95 citation statements)
references
References 15 publications
3
83
1
8
Order By: Relevance
“…Because the role of the LSP in pathogenesis of low back pain remains unclear, the findings of our study may have valuable clinical implications. Recently, ISPD have been used as an alternative solution to the conventional decompressive surgery for DDD, lumbar spinal stenosis caused by degenerative lumbar spondylolisthesis (DLS) [27,28]. Promising clinical outcomes have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the role of the LSP in pathogenesis of low back pain remains unclear, the findings of our study may have valuable clinical implications. Recently, ISPD have been used as an alternative solution to the conventional decompressive surgery for DDD, lumbar spinal stenosis caused by degenerative lumbar spondylolisthesis (DLS) [27,28]. Promising clinical outcomes have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Promising clinical outcomes have been reported. However, there are also studies reporting that the interspinous implants may result in complications, including implant migration and spinous process fracture [4,27,28]. Kim et al [27,29] indicated that degenerative lumbar spondylolisthesis appears strongly associated with the occurrence of spinous process fracture after interspinous process spacer (IPS) surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the most recent RCT by Stromquist et al reported no statistically significant difference between decompressive surgery (50 patients) and implantation of the X-Stop Ò (50 patients) after 2-year follow-up [22]. However, they found a significantly higher re-operation rate compared to non-instrumented surgery, as was, among others, also reported by Verhoof in 2008 [29] and Deyo in 2013 [30].…”
Section: Case Studiesmentioning
confidence: 74%
“…Mean surgery time for MID and X-STOP was 113 and 47 min, respectively. Reoperation rates due to recurrent symptoms were significantly higher for X-STOP than MID, however [11].…”
Section: This Article Is Part Of the Topical Collection On Motion Prementioning
confidence: 83%